Relasi Manusia, Alam dan Tuhan dalam Tradisi Madura Perspektif Immanuel Kant - Mukit, Abdul (Javano Islamicus, 2024)
This research examines Madurese ethics as a basis for building harmonious relationships between humans, nature and God, based on the social and cultural values ​​inherent in society. Through Im-Manuel Kant's transcendental and deontological ontological approach, using literature review research methods. This research analyzes the implementation of Madurese ethics in human interactions by highlighting the carok phenomenon which reflects social dynamics. In addition, the rokat tase' phenomenon shows a connection with nature, underlining the importance of balance and respect for the environment. In the context of the relationship with God, the samman phenomenon is an illustration of the application of ethical principles in the religious life of Madurese people. The findings of this research confirm the significance of Madurese ethics in forming harmonious and sustainable relationship patterns, in line with the universal rational principles put forward by Immanuel Kant.